Gorillas can dance : lessons from Microsoft and other corporations on partnering with startups - Prashantham, Shameen (John Wiley & Sons, Inc., 2022)
"Faced with disruption brought about by digitalization, multinational corporations are realizing the value of partnering with external actors--including start-ups. However, while established corporations and start-ups do have complementary capabilities that could result in win-win collaboration, they often find that developing productive partnerships is not straightforward. The very thing that attracts them to each other -- their significant differences -- also makes it difficult to work together. There, the partnering process must be approached not only enthusiastically but thoughtfully, by addressing these systemic asymmetries through focusing on the three pillars of synergy, interface, and exemplar. In this book, drawing upon over a decade of research in multiple locations -- including China, German, India, Israel, Kenya, South Africa, UK and US -- Professor Shameen Prashantham provides guidance on how corporations and startups can build mutual beneficial partnerships. Using examples such as Microsoft and several others including AB InBev, Bayer, BMW, Coca Cola, IBM, Intel, Nissan (Infiniti), SAP, Unilever and Walmart, among others, Gorillas Can Dance discussed the "why", "how", and "where" of corporation-startup up partnering. Readers will learn that to succeed in the age of digital disruption, companies need to develop entrepreneurial, collaborative, and global mindsets"--